ANALISIS PULANG POKOK USAHATANI BAWANG MERAH (Allium ascolonicum sp.) DI DESA LABUAN TOPOSO KECAMATAN TAWAELI KABUPATEN DONGGALA - Yulianti Kalaba; Lien Damayanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2007)
Shallot classified by a commercial commodity because most its yield production to fulfill market demand. Though itsconsumption in domestic not in gross as does rice, but in required big enough aggregate of society. Don’t make available or less isavailable of shallot commodity, and also its fluctuation can generate the disquiet in society. But that way farm shallot not yet fullcan be told to succeed, because of in its effort require the big expense, goodness fulfill the use of medium expense produce that isseed, manure, wide land and also labor cost requirement. This Input use will determine the level of production and level ofreleased expense. The objective of this research to know break even point farm shallot so that farmer in its interposing canestimate the of use of factor cost of production to use to obtain get the beneficial profit. Research executed in Countryside ofLabuan Toposo determined in intends the (purposive). Research responder specified by as much 28 KK from population as much56 KK or 50% by using random sample method modestly. Data collecting used by technique of questioner and investigation book.Model the analysis break even point to see the relation of between expense, acceptance and profit. The results showed theresponder of farm shallot experience break even point at production 72.40kg per season plant or equal to Rp506.800 at the time ofTR=TC. Where mean of sale acceptance (TR) of equal to Rp8.056.500 with the mean storey level produce equal to 1.150kgresiding in for total cost mean (TC) of equal to Rp2.571.235. Is thereby obtained by value R/C (Revenue Cost Ratio) equal to 3.08which its meaning each every expense use of equal to Rp100 will obtain get the acceptance of equal to 3.08. For that competentfarm shallot in developing because production and acceptance still reside in for dot come home fundamental.Keywords: Shallot, acceptance, expense, and break even point analyze.